Rectal biopsies: inaccuracy of histological grading in carcinoma of the rectum. - Smedley, F H (1984)
In a consecutive series of 70 patients with carcinoma of the rectum, 42 had operable tumours and in these the histology of the initial biopsy was compared with that of the excised specimen. In 9 of the 42 patients the histological grading of the original biopsy was different from that of the final specimen; in 3 the carcinoma was missed despite repeated preoperative biopsies; and in 5, errors were made in the diagnosis of carcinoma in polyps. In 5 of 7 cases of poorly differentiated carcinoma the initial biopsies indicated moderate differentiation: there was therefore a 70% inaccuracy in the preoperative diagnosis of poorly differentiated carcinoma of the rectum. The implications of this inaccuracy for the surgery of rectal cancer are discussed.